Electrospun nanofibers with chemotactic concentration gradient for tissue engineering applications - Handarmin (2012)
Engineered tissue acts as temporary construct that will be gradually replaced as the cells populate and remodel their own surrounding matrix. Laden with various cues, extracellular matrix (ECM) is cell-instructive in nature. The crosstalk between cells and ECM is, however, complex and still not emulated well by artificial scaffold due to the challenges in conferring the whole spectrum of cues. One of the challenges is to bestow chemotactic concentration gradient to implantable scaffold. The benefit is clear as cells naturally use chemotactic concentration gradient as guidance in migration and other directional processes such as neurite outgrowth. It has therefore become the aim of this project to bring this underutilized powerful factor into biomimetic electrospun fibers. We have established the methods of incorporating concentration gradient of nerve growth factor (NGF), as an example, into poly(e-caprolactone)-poly(ethyleneglycol) nanofibers by coaxial electrospinning. The existence of the gradient was verified qualitatively and quantitatively. Furthermore, we demonstrated the cytocompatibility of the scaffold, released NGF bioactivity, and cellular response to the encapsulated NGF concentration gradient with PC12 cells. In contrast to the use of synthetic polymers, harnessing the benefits of natural materials is more difficult. Lack of appropriate crosslinking technique for these hydrogel materials that could support endowed chemotactic cues necessitates the development of a new method. In attempt to address this issue, we directly encapsulated microbial transglutaminase (mTG) enzyme into electrospun gelatin fibers. The enzyme retained its catalytic capability, at least partially. We have also identified key crosslinking condition that allows the structure of majority the fibers to be preserved at physiological condition for prolonged period. Although the result is encouraging, it is still not suitable yet to have chemotactic concentration gradient implemented. In summary, we have successfully incorporated chemotactic concentration gradient into implantable electrospun nanofibrous scaffold and developed a promising novel method of crosslinking gelatin electrospun fibers by using mTG.